Analisis Sistem Tunjangan Profesi: Kunci Kesejahteraan Bagi Guru Pendidikan Agama Islam - Kurniasih, Siti Rohmah; Hermawan, A. Heris (Indonesia, 2023)
This research aims to explain the analysis of the professional allowance system, which includes policies regarding recipient criteria, allowance amounts, and allowance administration procedures for PAI teachers, as well as provide an overview of the welfare performance of PAI teachers before and after receiving professional allowances, so that in the future it is hoped that more and more teachers will PAI understand the professional allowance system so that it has an impact on fulfilling the welfare of PAI teachers. This research uses quantitative methods with a cross-sectional type of survey research. Research data sources consist of primary data sources originating from journal articles, books, and documents that are relevant to the research problem. Meanwhile, secondary data sources come from PAI teachers at the elementary school level in Kec. Dayeuhkolot District, Bandung, with 16 PAI teachers who have received professional allowances. The data collection technique uses a questionnaire or questionnaire distributed via Google Forms, which is analysed using descriptive statistics and presented in the form of narratives, tables, and diagrams. The results of the research show that the PAI teacher professional allowance system is explained in Minister of Religion Regulation Number 43 of 2014 Article 1 and Minister of Religion Regulation Number 43 of 2014 Article 8. Apart from that, the results showed that the welfare of PAI teachers after receiving professional allowances increased by 17.18%. So it can be concluded that professional allowances can be the key to PAI teacher welfare.